The Influence of Investment Knowledge, Financial Literacy, and Minimum Capital on Student Investment Interests at the Universitas Muhammadiyah Gresik Investment Gallery - Rafilah Maulidiya Ahmad; Anita Handayani; Wasti Reviandani (INNOVATION RESEARCH JOURNAL, 2023)
Investment has been in great demand in the modern era, starting from students to the public, now students are also starting to get to know investment with the existence of investment galleries that are starting to enter universities. But in fact, even though students have been given investment gallery facilities, an understanding of investment is very much needed before investing. The results of the pre-survey conducted by researchers show that management students at the University of Muhammadiyah Gresik in 2019-2020 are still unable to understand investment and its types. Many factors influence investment interest, including investment knowledge, financial literacy, and minimal capital. This study aims to determine the effect of investment knowledge, financial literacy, and minimal capital on investment interest in Management Students of the University of Muhammadiyah Gresik in the Investment Gallery. The research method uses quantitative research methods with a sample of 212 respondents. The data obtained were analyzed using multiple linear regression analysis using SPSS 20 program. The results showed that investment knowledge had a positive and significant effect on investment interest, financial literacy had a positive and significant effect on investment interest, and minimal capital had a positive and significant effect on investment interest. Keywords: Investment knowledge, Financial literacy, Minimum capital, and Investment interest.